Influence of material in sheet-bulk metal forming from coil - Leicht, Miriam; Merklein, Marion (Production Engineering, 2024)
Sheet-bulk metal forming (SBMF) represents an innovative approach for the efficient manufacturing of functional integrated parts from sheet metal by applying bulk forming processes to sheet metal. It combines the advantages of part weight optimization and process chain shortening. In view of the increasing demand for functionally integrated components, the forming from coil offers an economical possibility to produce high output rates. Nevertheless, an underfilling of functional elements as well as an asymmetric part forming are current challenges. In order to apply SBMF from coil in industrial contexts, it is necessary to understand the causes of these process limits and to develop measures for improving the forming of functional elements and thereby push existing forming limits. In this paper, both a lateral and a backward extrusion process from coil for the forming of internal and external geared SBMF parts are investigated to develop a fundamental process understanding. In a combined numerical-experimental approach, the influence of the flow behavior of different materials as well as the impact of the main material flow direction of the process on the dimensional part accuracy is analyzed. This enables the evaluation of fundamental material-related dependencies and influences regarding the geometrical part accuracy, the mechanical component properties and the tool load for forming of the conventional deep-drawing steel DC04 (t0 = 2 mm), a high-strength steel material (HC260LA) and an aluminum alloy (AA6082 T6). Based on these findings, measures for material flow control are identified and investigated to counteract the challenges of SBMF from coil. These findings permit the identification of potential transferability of the identified cause-effect mechanisms to different processes, component geometries and materials. Thereby, in particular, an increase in coil width as well as lower a strain hardening behavior of the material offers the possibility to improve the geometrical accuracy of the components.
CRIS-Team Scopus Importer:2024-08-16
Keywords: Cold Forming; Extrusion; Sheet-bulk metal forming